FIB-5 versus FIB-4 index for assessment of hepatic fibrosis in chronic hepatitis B affected patients - Metwally, Khaled (Clin Exp Hepatol, 2020)
AIM OF THE STUDY: Chronic hepatitis B virus (HBV) infection is one of the major health problems worldwide. Use of non-invasive tests for assessment of hepatic fibrosis such as the FIB-4 index could be used to avoid liver biopsy. Another promising noninvasive test, FIB-5, could also be used to detect significant hepatic fibrosis. The aim of the study was to compare the use of FIB-5 and FIB-4 as noninvasive markers to assess chronic HBV-related hepatic fibrosis. MATERIAL AND METHODS: This study was done on 176 chronic HBV patients who underwent liver biopsy. Grading and staging of liver fibrosis was done according to the METAVIR scoring system. FIB-5 and FIB-4 scores were calculated for all patients. RESULTS: As regards FIB-4 for differentiation between non-significant fibrosis (group I) and significant fibrosis (group II), at a cutoff level of 1.28 with positive predictive value (PPV) 41.4% and specificity 48% while at a cutoff level of 7.08 with PPV 98.8% and specificity 98% for FIB-5. CONCLUSIONS: As regards both scores, the FIB-5 score was more specific than FIB-4 for diagnosing significant from nonsignificant hepatic fibrosis in patients with chronic HBV infection.